QUALITY OF INPATIENT MEDICAL RECORDS AT HAI DUONG MEDICAL TECHNICAL UNIVERSITY HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of inpatient medical record recording quality according to the medical record sub-item recording standards prescribed by the Ministry of Health.Subjects and methods: This cross-sectional study was conducted on 268 inpatient medical records at Hai Duong Medical Technical University Hospital from January 2023 to December 2023.Results: When assessing individual items, the general information section of the medical records was recorded with high accuracy and completeness, such as full name, date of birth, and sex of patients (98-99.3%). Healthcare staff adhered to detailed documentation without abbreviations in the administrative section in 92.2% of cases. However, some items were documented with notably low rates, for example, specific and detailed address information was recorded completely in only 6% of cases. Most of the criteria in the section on the status of recording the content of performing paraclinical indications in medical records reached over 90%, the lowest comprehensive medical order criterion is 87.3%. The section of care card of 76.1%.Conclusion: From the research results, it is necessary to prioritize monitoring and focus on these shortcomings in medical record recording to enhand the quality of records for future assessment.
Keywords: Medical records, hospital, inpatient.